Quantum cascade laser light propagation through hollow silica waveguides - Francis, Daniel; Hodgkinson, Jane; Livingstone, B.; Tatam, Ralph P. (Springer, 2015)
In this paper, the transmission characteristics of hollow silica waveguides with bore diameters of 300 and 1000 μm are investigated using a 7.8-μm quantum cascade laser system. We show that the bore diameter, coiling and launch conditions have an impact on the number of supported modes in the waveguide. Experimental verification of theoretical predictions is achieved using a thermal imaging camera to monitor output intensity distributions from waveguides under a range of conditions. The thermal imaging camera allowed for more detailed images than could be obtained with a conventionally used beam profiler. The results show that quasi-single-mode transmission is achievable under certain conditions although guided single-mode transmission in coiled waveguides requires a smaller bore diameter-to-wavelength ratio than is currently available. Assessment of mode population is made by investigating the spatial frequency content of images recorded at the waveguide output using Fourier transform techniques.